2010
DOI: 10.1007/s12029-009-9124-5
|View full text |Cite
|
Sign up to set email alerts
|

OGG1 Ser326Cys Polymorphism and Susceptibility to Esophageal Cancer in Low and High At-Risk Populations of Northern India

Abstract: OGG1 Ser326Cys polymorphism does not have a role in determining susceptibility to esophageal cancer either in high or in low at-risk populations of Northern India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…However, studies by Guo et al [18] and Wang et al [17] in Chinese population included only ESCC histology patients, but still showed significant association. The incongruity with Chinese reports from ours may be due population/ethnic variations which are also evident in our previous studies [28,29]. Similar to our report, a study in head and neck cancer by Liu et al [12] in Caucasian population showed combined risk genotypes of common SNPs in pre-miRNAs were associated significantly with increased risk of SCC of head and neck cancer.…”
Section: E16supporting
confidence: 64%
“…However, studies by Guo et al [18] and Wang et al [17] in Chinese population included only ESCC histology patients, but still showed significant association. The incongruity with Chinese reports from ours may be due population/ethnic variations which are also evident in our previous studies [28,29]. Similar to our report, a study in head and neck cancer by Liu et al [12] in Caucasian population showed combined risk genotypes of common SNPs in pre-miRNAs were associated significantly with increased risk of SCC of head and neck cancer.…”
Section: E16supporting
confidence: 64%
“…In present study, we did not find any association of CASP8 −652 6N del polymorphism with ESSC or its clinical characteristics in northern Indian population. This discrepancy may be related to vast difference in incidence of EC in Chinese and northern Indian populations ensuing difference in genetic make‐up and thus in genetic association of EC between two populations as previously reported 33, 34. Similar to our finding, Haiman et al 35 also did not find any association of CASP8 −652 6N del variant with breast, colorectal, and prostrate cancers in multiple populations of various ancestries, contradictory to prior report by Sun et al 14 Likewise, several other reports also failed to replicate purported association with different cancers supporting our hypothesis of population‐specific nature of association 18, 20, 36.…”
Section: Discussionmentioning
confidence: 86%
“…In a preliminary search, we identified 58 research articles related to OGG1 Ser326Cys polymorphism and the risk of head and neck, oral, pancreatic, gallbladder, colorectal and gastric cancers. Among all the articles identified, only 31 were subjected to further examination out of which only 17 (Kumar et al 2011 ; Canbay et al 2011 ; Srivastava et al 2009 ; Gorgens et al 2007 ; Laantri et al 2011 ; Sameer et al 2012 ; Sliwinski et al 2011 ; Li et al 2013 ; Upadhyay et al 2010 ; Canbay et al 2010 ; Palli et al 2010 ; Engin et al 2011 ; Curtin et al 2009 ; Przybylowska et al 2013 ; Pardini et al 2008 ; Li et al 2009 ; Srivastava et al 2010 ) were found to meet the inclusion criteria (Table 1 ). Many of them were removed from the study due to lack of detailed information of all the genotypes and also due to non accordance of the controls with the Hardy–Weinberg equilibrium.…”
Section: Resultsmentioning
confidence: 99%